Training Tourism Planners; Case Study Of The Tourism Planning Programme At Universiti Teknologi Malaysia - Hamzah, Amran; Khalifah, Zainab; Dahlan, Nor Azlina (2012)
This paper attempts to present a case study of the only postgraduate taught course in tourism planning in Malaysia. It will summarise thefundamentals of the programme including the course content and teaching methods. More importantly,it will discuss the problems encountered in an attempt to improve the marketability of the programme and subsequently highlight measures being taken to remedy this situation.